2011
DOI: 10.1029/2010jb007993
|View full text |Cite
|
Sign up to set email alerts
|

Seismic variability of subduction thrust faults: Insights from laboratory models

Abstract: [1] Laboratory models are realized to investigate the role of interface roughness, driving rate, and pressure on friction dynamics. The setup consists of a gelatin block driven at constant velocity over sand paper. The interface roughness is quantified in terms of amplitude and wavelength of protrusions, jointly expressed by a reference roughness parameter obtained by their product. Frictional behavior shows a systematic dependence on system parameters. Both stick slip and stable sliding occur, depending on dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 85 publications
(130 reference statements)
4
58
0
Order By: Relevance
“…Baumberger et al, 1994). A similar transition from potentially seismic to aseismic behaviour has been speculatively applied to subduction megathrusts, where the observed earthquake magnitude decreases with depth and the subsequent switch off at the downdip limit of the seismogenic zone may be explained by a progressive decrease in the viscosity of the upper plate (Namiki et al, 2014) or by the progressive smoothing of the interplate roughness (Voisin et al, 2008;Corbi et al, 2011).…”
Section: Seismic Versus Aseismic Faultingmentioning
confidence: 69%
See 3 more Smart Citations
“…Baumberger et al, 1994). A similar transition from potentially seismic to aseismic behaviour has been speculatively applied to subduction megathrusts, where the observed earthquake magnitude decreases with depth and the subsequent switch off at the downdip limit of the seismogenic zone may be explained by a progressive decrease in the viscosity of the upper plate (Namiki et al, 2014) or by the progressive smoothing of the interplate roughness (Voisin et al, 2008;Corbi et al, 2011).…”
Section: Seismic Versus Aseismic Faultingmentioning
confidence: 69%
“…In their foam models, Brune et al (1990) found a high periodicity of recurring characteristic stick-slip events with a CV ∼ 10 %. Similarly, elastic sliders by Corbi et al (2011) or stick-slip of granular materials as shown in Fig. 10 generally display regular stick-slip with minimal variability in size and frequency given that extrinsic factors (load, loading rate) are kept constant.…”
Section: Earthquake Statisticsmentioning
confidence: 98%
See 2 more Smart Citations
“…The gelatin itself is a specifically calibrated material-gelatin with 2.5 weight percent pig skin-created for such models based on the study of the rheological and physical properties of a wide range of materials. The subduction megathrustthe plate interface-is made of gelatin on sand-paper and gelatin on plastic to scale the boundary's velocity-weakening and velocitystrengthening frictional behaviors, respectively [Corbi et al, 2011].…”
Section: Modeling Seismic Behaviormentioning
confidence: 99%